TATA ULANG LAHAN PARKIR PADA JALAN KALIMANTAN KOTA LUBUKLINGGAU - Noperiyadi nazif (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2015)
The increase of activities particularly shopping centers at Kalimantan Street of Lubuklinggau City, requires sufficient supply of parking facility. However, so far there is no study on parking characteristics and quantification of standard parking spaces demand. The objectives of this study are to evaluate parking characteristics on shopping centers at Kalimantan Street of Lubuklinggau City and to analyse standard of parking spaces demand. For Pos 1 off street parking, the parking capacity was for motor cycle (50 vehicles), for Pos 2 on street parking, the parking capcity was for car (13 vehicles), for Pos 3 on street parking, the parking capacity was for car (14 vehicles), for Pos 4 on street parking, the parking capacity was for motor cycleÂ (60 vehicles), for Pos 5 on street parking, the parking capacity was for motor cycleÂ (60 vehicles) and for Pos 6 on street parking, the parking capacity was for car (30 vehicles). Result of parking characteristics analyses, we are will be obtained parking accumulation, parking volume, parking turn over, parking index, parking duration and parking capacity. From result of parking characteristics analyses can do for design of parking at Kalimantan Street of Lubuklinggau City. Key Words : Parking Characteristics Analyes, Demand, Shopping Centers, Design ofÂ Parking